Phototherapy for early-stage mycosis fungoides in thais - T. Sukakul (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND. Objective: To study the efficacy of psoralen with ultraviolet A photochemotherapy (PUVA) and narrowband ultraviolet B phototherapy (NBUVB), for early-stage mycosis fungoides (MF) in Thais. Materials and Methods: A retrospective medical chart review of 50 cases was performed. Demographic data, type of phototherapy, duration of treatments, clinical response, relapse, and adverse effects were analyzed. Comparative analysis of clinical response between hypopigmented MF and non-hypopigmented MF was performed. Results: Fifty MF patients that were stage Ia to Ila were evaluated. Fifty-four percent of patients were treated with NBUVB, 20.0% with PUVA, 6.0% with ultraviolet A1, and 20.0% with combined phototherapy. Mean treatment duration was 7.0±2.3 months for PUVA and 7.6±4.4 months for NBUVB. Thirty patients (60.0%) had complete response and 17 (34.0%) had partial response. Clinical response between PUVA and NBUVB was not significantly different, however PUVA had less cases of relapse. Clinical response was better for hypopigmented MF patients than for non-hypopigmented MF patients. Conclusion: PUVA and NBUVB are effective and safe for early-stage MF. Hypopigmented MF had better clinical response than non-hypopigmented MF.